Assessment of Safety Culture and the Evaluation of the Effect of Education on the Improvement of Safety in the Metal Industry during 2018 - parvin sepehr; Nayera Naimi Ghasabiyan (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: Lack of a safety culture in organizations is the main reason for the occurrence of accidents. This phenomenon is formed in an improper safety management system and an inappropriate safety culture. One of the ways to improve the culture of safety is education. Therefore, this study aimed at investigating the promotion of safety culture and the impact of education on this culture. Methods: The present study was conducted on all employers working at Ekbatan Metal Industry to evaluate the safety culture using a questionnaire with the aim of promoting safety. The obtained data were analyzed in Excel and SPSS software (version. 19) through statistical tests. The training sessions were held and the safety culture was then    evaluated after the intervention. Ultimately, a comparison was made between the scores of safety culture and its ten dimensions before and after the  intervention. Results: The mean value of safety culture before the intervention was obtained at 287 and ten dimensions of the safety culture were  investigated individually. The mean scores of safety culture obtained from the employers and workers were 290.67±26.17 and 283±47.25, respectively, before the intervention. However, the mean score of safety culture was 318±31.11 after the intervention. Conclusion: The results showed that education is one of the effective ways to promote safety culture. Education on safety can have a significant effect on the promotion of safety culture. Therefore, it is necessary to develop and implement educational programs based on the needs analysis. It is recommended to monitor these programs continuously and implement them in high-risk contexts.